The Northern Forests of Iran Along the Caspian Coast - Mossadegh, A. (Indian Forester, 1974)
The Northern Forests of Iran along the Caspian Coast Iran has a total area of about 1650000 square kilometers. The Caspian forests cover about 3500000 hectares, creating a very interesting and valuable area of activity for today's research men as well as for those of tomorrow. A biotic factors of the region comprises of 1-Climatic factors, 2-Precipitation 3-Temperature 4-Snow. The Biotic characteristics comprises of 1-Edaphic factors 2-Animal life of the forest. The natural forest of the Caspian zone from the ridge of the Elburz up the Caspian sea comprises of the following communities. I. Carpinetum orientale II. Fagetum hyrcanum III. Parrotio carpinetum IV. Querco carpinetum V. Querco buxetum. The Caspian forest is a zone of most valuable and economical beech forests.